α-SiAION: Development and machining test on gray cast iron - Silva, O. M M; Nono, M. C A; Souza, J. V C; Ribeiro, M. V. [UNESP] (Trans Tech Publications, 2008)
The α-SiAlON ceramic cutting tool insert is developed. Silicon nitride and additives powders are pressed and sintered in the form of cutting tool inserts at temperature of 1900 °C. The physics and mechanical properties of the inserts like green density, weight loss, relative density, hardness and fracture toughness are evaluated. Machining studies are conducted on grey cast iron workpiece to evaluate the performance of α-SiAlON ceramic cutting tool. In the paper the cutting tool used in higher speed showed an improvement in the tribological interaction between the cutting tools and the grey cast iron workpiece resulted in a significant reduction of flank wear and roughness, because of better accommodation and the presence of the graphite in gray cast iron. The above results are discussed in terms of their affect at machining parameters on gray cast iron.
Keywords: α-SiAlON; Ceramics; Cutting tool; Flank wear; Hardness; Sintering; Cutting tool inserts; Gray cast irons; Green densities; Grey cast irons; Machining parameters; Machining tests; Relative densities; Significant reductions; Tribological interactions; Weight losses; Work pieces; Ceramic cutting tools; Ceramic materials; Ceramic tools; Cutting tools; Density (specific gravity); Fracture; Fracture toughness; Graphite; Machine tools; Machining; Mechanical properties; Metal casting; Metal working tools; Nitrides; Powders; Silicon nitride; Toughness; Cast iron